Photonics in a Time of Rapid Growth: Silicon Based Optoelectronics in China - Zhiping Zhou; Weibiao Chen; Xiwen He; Deyue Ma (IEEE Photonics Journal)
Silicon-based optoelectronics (SBO), combining the advantages of both microelectronics and optoelectronics, has entered a period of rapid development. Applications based on SBO have expanded from traditional communication field to other fields such as sensing, computing, and artificial intelligence. Although the SBO technology started relatively late in China, it has developed rapidly in recent years due to continuous investment and improved industrial structure. This article first reviews the early activities, and then, summarizes the current status of SBO in China. It provides a comprehensive analysis of academic and industrial advancements in recent years and discusses future development directions and main challenges.